‘Our heart that burned’: Israel is wiping out centuries of heritage in southern Lebanon - Walid El Houri (Global Voices, 2024)
As thousands are killed and wounded in Israel’s ongoing genocide in Palestine and brutal attacks on Lebanon, the urgent need to save lives and cope with trauma often overshadows the devastating loss caused by the systematic destruction of heritage, memory, and history.